Electret Microphone and Counts Statistic in Monitoring 3D Printing - Barbosa, Luanne [UNESP]; Lopes, Thiago Glissoi [UNESP]; Aguiar, Paulo Roberto [UNESP]; De Carvalho Monson, Paulo Monteiro [UNESP]; de Oliveira, Reinaldo Götz [UNESP]; de Oliveira Conceição, Pedro (Institute of Electrical and Electronics Engineers (IEEE), 2023)
The additive manufacturing process commonly referred to as the 3D printing process, requires effective monitoring of the initial layer printing to ensure successful part fabrication. It is possible to achieve this by using acoustic sensors such as the electret microphone, which are widely used and cost-effective measuring devices renowned for their precision. Mounting the sensor onto the extruder of the printer has been demonstrated to be effective in capturing signals that accurately represent the process. Nevertheless, further research is necessary to explore new methods of processing and analyzing these signals to fully realize the microphone's potential. The Counts method is a trustworthy technique for measuring the activity of a signal above a predetermined threshold. The present study aims to examine the electret microphone's response to the manufacturing of a monolayer square part while evaluating the efficacy of the Counts method in capturing the key features of the sensor's signals, thereby enabling the monitoring of the 3D printing process. Two specific defects, filament running out during printing and extruder nozzle clogging during printing, were generated from the normal pattern. Results confirm that mounting the electret microphone to the printer's extruder generates less noisy signals than alternative placements, consistent with previous research. Moreover, using the Counts method and selecting an appropriate frequency band allows the sensor to differentiate between conditions; clogging reduces the signals' amplitude, while filament lack increases it. In conclusion, the electret microphone is an efficient tool for monitoring 3D printing when mounted to the printer's extruder, and the Counts method effectively captures the signal's key features.
Keywords: 3D printing; counts; Electret microphone; monitoring; signal processing